Adolescent Dropouts in Balantang Malili Village, East Luwu Regency: (Sociology of Education Study - ABDUL MALIK ISKANDAR; Jalal Jalal; Akhiruddin Akhiruddin; Harifuddin Harifuddin; Andi Herlina (Hasanuddin Journal of Sociology, 2022)
This study aims to analyze the lives of out-of-school children in adolescents in Balantang Village, Malili District, East Luwu Regency. How is the life of out-of-school teenagers in Balntang Village, Malili District, East Luwu Regency? Why do teenagers of productive age in Balantang Village, Malili Subdistrict, East Luwu Regency choose to drop out of school? This study uses a qualitative approach. The main informants consisted of children who had dropped out of school as many as 9 people and the key information consisted of school principals, parents and 4 community leaders. Data collection techniques used are in-depth interviews, respondent observations and available documents and literature study. Using data reduction analysis, data presentation and data validity of researcher bending, triangulation, time extension, Focus Group Discussion. In-depth analysis. The results showed that children who dropped out of school were caused by many factors, including family, peers, economy, living environment, school environment. The conclusion of the research is that children who drop out of school and are unemployed have two behaviors: 1. Negative behavior such as hanging out, drinking alcohol, fighting between teenagers, forming gangs. Positive behaviors such as helping people earn a living, and choosing their own jobs